Essential Threats to the Security of the GCC Countries in the Post Arab Spring Era. (May 2015) - Binhuwaidin, Mohamed M.
Abstract The so called Arab Spring has brought more challenges to the security of the Arabian Gulf states members of the Gulf Cooperative Council (GCC). This article aims to reach a better understanding of the main threats facing the GCC states in the post Arab Spring era. It argues that the conservative system of the GCC states, originated in the paternalistic conservatism, is facing an essential threat from three very important elements that are instigated by the eruption of the so called Arab Spring: political liberal ideas, political Islamic movement, and sectarianism. The article investigates the impact of these elements on the GCC states.